Genome-wide association study and genomic prediction for pod-shattering tolerance in a diverse rapeseed/canola germplasm collection - Shakil Hosain; David P. Horvath; Jayanta Roy; Ahasanul Hoque; Muhammad Arifuzzaman; Mukhlesur Rahman (Euphytica, 2025)
Pod-shattering in rapeseed/canola results in significant yield loss. In this study, a diverse spring-type rapeseed/canola germplasm consisting of 146 accessions was evaluated for pod-shattering tolerance in five environments under field and greenhouse conditions. The genome-wide association study (GWAS) was conducted using 24K single nucleotide polymorphisms (SNPs) markers obtained through genotyping-by-sequencing (GBS). Eight GWAS approaches were employed which identified 21 SNPs for pod-shattering. The phenotypic variation explained by these SNPs ranged from 3.8 to 25.4%. The SNP positions located on chromosomes A01, A03, A05, A06, A09, C02, C03, C05, and C08 have been previously reported to be associated with shattering. Two strong candidate genes, INDEHISCENT ( IND ) and MANNANASE7 ( MAN7 ), located on chromosome A03 (20.5 Mbp position) and chromosome C04 (61.1 Mbp position), respectively, were identified for the pod shattering trait. Genomic prediction (GP) was conducted with 24K SNPs using 14 prediction models. The prediction ability of all models ranged from 0.18 to 0.50 across five different environments. To determine the minimum number of markers needed to estimate the predictive ability, we used 25 to 20,000 randomly selected markers where 3000 to 20,000 markers gave a similar prediction ability (≈0.47). This study provides significant insight and elevates our understanding of the genetic architecture of pod-shattering in canola and suggests that SNP markers and GP have the potential to select pod shattering resistant germplasm at an early stage for use in a breeding program.

Identification of QTLs for symbiotic nitrogen fixation and related traits in a soybean recombinant inbred line population - C. Bennet Krueger; Jeffery D. Ray; James R. Smith; Arun Prabhu Dhanapal; Muhammad Arifuzzaman; Fei Gao; Felix B. Fritschi (Theoretical and Applied Genetics, 2024)

Transcriptome Analysis Suggests Cytokinin and Gibberellin Signaling May Account for Differences Between Spring and Winter Canola (Brassica napus L.) Root Development - Muhammad Arifuzzaman; David Horvath; Mukhlesur Rahman (Journal of Plant Biology, 2022)

Genome wide association mapping and candidate gene mining for root architectural traits in rapeseed/canola (Brassica napus L.) at late growth stage - Muhammad Arifuzzaman; Mukhlesur Rahman (Euphytica, 2020)

Shovelomics for phenotyping root architectural traits of rapeseed/canola (Brassica napus L.) and genome-wide association mapping - Muhammad Arifuzzaman; Atena Oladzadabbasabadi; Phillip McClean; Mukhlesur Rahman (Molecular Genetics and Genomics, 2019)